Joint audit and its impact on the market value of firms listed on the Iraq Stock Exchange - Faris, Ashraf Hashem; jasim, muthana rokan; salem, Ayad dakheel (Journal of Economics and Administrative Sciences, 2020)
The research aims to investigate the possibility of joint auditing in improving the market value of Iraqi companies listed on the Iraq Stock Exchange. The sample was represented by 10 Iraqi companies listed in the Iraq market for the period from 2014-2017 (2 years before implementation and 2 years after implementation) and the research was based on the idea that joint auditing enhances investor confidence and raises their level of security as a result of providing quality and reliable reports, and thus This indicates good news in the market that reflects on the performance of stocks and the market value of companies that adopt joint auditing. The results of the analysis indicate an improvement in the market value, but this improvement is not due to the application of joint auditing, so it was concluded that the mandatory application of joint auditing does not have a significant impact on the market value, but this is due to the improvement in the performance of companies, and the research recommends that the concerned bodies should not be obligated to audit companies The question of its application is voluntary, to reflect the companies' intentions to improve the quality of their reports.